The economic impact of violence perpetration in severe mental illness: a retrospective, prevalence-based analysis in England and Wales - Morwenna Senior, MBBS; Seena Fazel, ProfMD; Apostolos Tsiachristas, PhD (Elsevier, 2020)
Summary: Background: Calls for increased funding for mental health services require many lines of evidence in support, including estimates of economic impact. One understudied source of cost is violence perpetrated by individuals with severe mental illness. Estimating this economic impact can inform budget planning across several government sectors and emphasise the importance of violence prevention. Therefore, we aimed to provide a comprehensive estimate of the economic costs of violence perpetrated by people with severe mental illness. Methods: For this retrospective analysis, we used a prevalence-based modelling approach to estimate the annual economic cost of violent incidents committed by people with severe mental illness in England and Wales during 2015-16. The model was based on secondary data, including the association between violence and severe mental illness, illness prevalence, recidivism, absolute numbers of violent incidents in 2015-16, and costs to society per violent crime, by area of spending. Uncertainty was addressed with probabilistic and deterministic sensitivity analyses that tested the effect of underreporting of domestic violence and distributions of crime types in individuals with severe mental illness. Outcomes: The estimated annual economic impact of violence perpetrated by people with severe mental illness was £2·5 (95% CI 1·4-4·5) billion in England and Wales in 2015-16, or 5·3% of the total estimated societal cost of violence. The largest contributors to the cost of violent crime perpetrated by individuals with severe mental illness were the cost of physical and emotional harm to victims (£1·4 [95% CI 0·8-2·5] billion), followed by lost productivity of victims (£348.0 [190·0-628·8] million), while the combined cost to the police and criminal justice system was £561·3 (305·9-1009·2) million and the cost to health services was £136·7 [74·3-246·3] million. The additional cost to secure forensic care was estimated to be £487·7 (302·0-709·1) million. Interpretation: The economic impact of violence perpetrated by individuals with severe mental illness is potentially important. Preventing violence, especially through services for individuals with comorbid substance misuse, and reducing recidivism might lead to cost savings at a governmental and individual level, in addition to the clinical and societal benefits. Funding: Wellcome Trust, National Institute for Health Research (NIHR) Oxford Biomedical Research Centre, and NIHR Applied Research Collaboration Oxford and Thames Valley.